В решении.
Объяснение:
с -3 -2 -1
2с +3 2*(-3)+3= -3 2*(-2)+3= -1 2*(-1)+3 = 1
2(с+3) 2*(-3+3)=0 2*(-2+3)=2 2*(-1+3)=4
(2с)²-3 (2*-3)²-3=33 (2*-2)²-3=13 (2*-1)²-3=1
2(с²-3) 2*((-3)²-3)=12 2*((-2)²-3)=2 2*((-1)²-3)= -4
с 0 1 2 3
2с+3 0+3=3 2*1+3=5 2*2+3=7 2*3+3=9
2(с+3) 2*(0+3)=6 2*(1+3)=8 2*(2+3)=10 2*(3+3)=12
(2с)²-3 (2*0)²-3= -3 (2*1)²-3=1 (2*2)²-3=13 (2*3)²-3=33
2(с²-3) 2*(0²-3)= -6 2*(1²-3)= -4 2*(2²-3)=2 2*(3²-3)=12
sin^2 3x+3 cos^2 3x-4 sin (П/2+3х) cos(П/2+3х)=0
sin^2 3x+3(1- sin^2 3x) -2 *2sin2(П/2+3х)=0
sin^2 3x+3-3sin^2 3x - 4cos2x = 0
-2sin^2 3x - 4( cos^2 x-sin^2 x)= 0
-2sin^2 3x -4cos^2 x + 4sin^2x=0
2sin^2 x -4(1-sin^2x)=0
2sin^2 x - 4 +4sin^2 x=0
6 sin^2 x=4
sin^2x=4/6
sin^2 x=2/3
sinx=2/3 sinx=-2/3
x=(-1)^n arcsin(2/3)+Пn x=(-1)^n arcsin(-2/3)+Пn
x=(-1)^n -arcsin(2/3)+Пn
x=(-1)^n+1 arcsin(2/3)+Пn
Сложим оба уравнения и получим: -4x = -36, откуда х = 9.
Подставим Х в любое из уравнений и получим У = 7.